2014
DOI: 10.1016/j.ajic.2014.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Trends in racial/ethnic disparities in influenza vaccination coverage among adults during the 2007-08 through 2011-12 seasons

Abstract: Background Annual influenza vaccination is recommended for all persons ≥6 months. The objective of this study is to assess trends in racial/ethnic disparities in influenza vaccination coverage among adults in the United States. Methods We analyzed data from the 2007-2012 National Health Interview Survey (NHIS) and Behavioral Risk Factor Surveillance System (BRFSS) using the Kaplan-Meier survival analysis procedure to assess influenza vaccination coverage by age, presence of medical conditions, and racial/eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 30 publications
7
58
0
Order By: Relevance
“…Long-standing differences in both influenza and pneumococcal vaccination coverage have been reported between community-dwelling black and white persons ≥65 years, even after adjustment for access to care and other socio-economic factors. 3337 These differences have been attributed to resistant attitudes and beliefs about vaccination, fewer vaccine-seeking behaviors, poorer provider communication, and less effective provider recommendations among blacks. 34,3839 In the current study, while vaccine refusal was the most common reason for non-vaccination in white and non-white residents, disparities in access to vaccination likely played a role in lower vaccination coverage among non-white residents, as these residents were more likely than unvaccinated white residents to report not being offered influenza and pneumococcal vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-standing differences in both influenza and pneumococcal vaccination coverage have been reported between community-dwelling black and white persons ≥65 years, even after adjustment for access to care and other socio-economic factors. 3337 These differences have been attributed to resistant attitudes and beliefs about vaccination, fewer vaccine-seeking behaviors, poorer provider communication, and less effective provider recommendations among blacks. 34,3839 In the current study, while vaccine refusal was the most common reason for non-vaccination in white and non-white residents, disparities in access to vaccination likely played a role in lower vaccination coverage among non-white residents, as these residents were more likely than unvaccinated white residents to report not being offered influenza and pneumococcal vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Lower influenza and pneumococcal vaccination coverage has been reported among community-dwelling Hispanics aged ≥65 years compared with their non-Hispanic white counterparts. 3335,37,40,41 Unlike non-Hispanic black adults aged ≥65 years, studies have found that Hispanics aged ≥65 years were less likely than non-Hispanic whites to report resistant attitudes toward vaccination, but more likely to report that they did not know these vaccines were recommended for them, suggesting that poor communication or language barriers might contribute to lower vaccination coverage in this population. 34,38 …”
Section: Discussionmentioning
confidence: 99%
“…Adults show generally similar immunization patterns, with the highest rates among non-Latino whites (96,152). Influenza disparities partly reflect differences in attitudes toward influenza vaccines (154) and active vaccination seeking (59).…”
Section: Preventive Carementioning
confidence: 90%
“…These rates remain below the national Healthy People 2020 target of 70% influenza vaccination coverage for adults and children [3]. Furthermore, racial/ethnic differences in influenza vaccination coverage have been persistent, with coverage being even lower for some racial/ethnic groups [4,5]. …”
Section: Introductionmentioning
confidence: 99%